2020
DOI: 10.12681/bgsg.22842
|View full text |Cite
|
Sign up to set email alerts
|

Rock-Eval analysis and organic petrographical characterization of the Upper Jurassic Naokelekan Formation, northern Mesopotamian basin, Kurdistan Region-Iraq

Abstract: The aim of this study is to assess the type, thermal maturity and the petroleum generation potential of the Upper Jurassic Naokelekan Formation, occurring across the Kurdistan Region of Iraq, by applying organic petrographical methods and Rock-Eval analysis. The Rock-Eval data would indicate the presence of kerogen types III, IV and II as the main constituents. However, the qualitative petrographical evaluation revealed that the main organic constituents are solid hydrocarbons, in the form of microgranular mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The organic matter of the Naokelekan Formation was recognized as Types II and III kerogen (Othman, 1990;Al-Atroshi et al, 2019), or Types III and IV (Abdula et al, 2020). This kerogen was described as mature and within the oil generation window in Sargelu locality (Baban and Ahmed, 2014).…”
Section: Organic Matter In the Naokelekan Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The organic matter of the Naokelekan Formation was recognized as Types II and III kerogen (Othman, 1990;Al-Atroshi et al, 2019), or Types III and IV (Abdula et al, 2020). This kerogen was described as mature and within the oil generation window in Sargelu locality (Baban and Ahmed, 2014).…”
Section: Organic Matter In the Naokelekan Formationmentioning
confidence: 99%
“…The sequence stratigraphic setting exposed by Balaky (2015), placing the upper part of the Naokelekan Formations as HST, would secure a suitable condition for impregnation of bitumen in the limestone and dolomite strata. The evaluation of organic matter presented by Abdula et al (2020) implied that the bitumen in the Naokelekan Formation is mainly migrated (migra-bitumen) and partly formed through heating (pyro-bitumen) of ancestor organic matter during maturation stages. As for the current case, it is believed that bitumen injection into the Naokelekan Formation followed fracturing of deeply seated hydrocarbon reservoir that received hydrocarbon from early Jurassic or older source rocks.…”
Section: Organic Matter In the Naokelekan Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their economic interest, these carbonate platforms and intrashelf basin successions have been studied from palaeogeographic and sequence stratigraphy points of view (Al‐Mojel et al, 2018; Hughes, 2004; Sadooni, 1997; Sharland et al, 2001; Ziegler, 2001). However, some intrashelf basins, such as the Sargelu or Gotnia Basin (present Kurdistan Region of northern Iraq) and Hawraman Basin (Hawraman region in NW Iran; Figure 1a), have received less attention, and most studies, specifically in Kurdistan, have been limited to facies analysis and source rock studies (e.g., Kirkuk and Hamrin oilfields; Abdula, 2015, 2017; Abdula, Balaky, Nurmohamadi, & Piroui, 2015; Abdula et al, 2020; Balaky, 2004; Hakimi, Najaf, Abdula, & Mohialdeen, 2018; Jassim & Buday, 2006; Salae, 2001). Predominant carbonates and shales were deposited during the Middle and Late Jurassic in these intrashelf basins (i.e., Sargelu, Najmah, and Gotnia formations in Hawraman Basin in NW Iran; Sargelu, Naokelekan, and Barsarin formations in Sargelu [Gotnia] Basin in the Kurdistan region of Iraq; Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Abdula et al [9] studied the petrographical features of organic matter from upper Jurassic Naokelekan Formation, Kurdistan-Iraq. Abdula et al [10] through the Rock-Eval analysis and organic petrographical characterization of the upper Jurassic Naokelekan formation, northern Mesopotamian basin, Kurdistan region-Iraq, evaluated the formation and concluded that the Naokelekan Formation contains types II and III kerogen. Abdula et al [11] studied the hydrocarbon potentiality and depositional environment of Naokelekan Formation in Binari Serwan-1 Well, NE-Iraq using infrared factors and palynological analysis evidence.…”
Section: Introductionmentioning
confidence: 99%